Techno-Economic Feasibility of SME-based Nickel Slag Valorization in Supporting Circular Industrial Development in Indonesia - Sawarni Hasibuan; H Thaheer; HH Purba (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Indonesia’s rapid growth in nickel processing has led to a significant increase in nickel slag from pyrometallurgical operations. While slag buildup creates environmental and land-use problems, using it in downstream production by small- and medium-sized enterprises (SMEs) has not been studied much. This study examines the technical and financial feasibility of producing paving blocks from nickel slag in a semi-mechanical SME production system. The process uses 85% slag, 10% fly ash, and 5% cement, with a planned capacity of 1,800,000 units per year. The technical review covers material processing steps, equipment details, and steady-state operating capacity. Financial analysis is done over 10 years with a 10% discount rate and standard capital budgeting methods. The total investment needed is IDR 2.16 billion. Results show strong financial performance, with a Net Present Value (NPV) of IDR 4.13 billion, an Internal Rate of Return (IRR) of 25.40%, a Benefit–Cost ratio of 2.91, and a payback period of 30.84 months. The break-even point is 279,886 units, or 21.53% of capacity, showing the system can handle moderate market stress. These results show that the use of SME-based slag is both technically feasible and economically sound, supporting small-scale industrial cooperation and offering a practical way to promote circular integration in Indonesia’s nickel industry. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 8: Decent Work and Economic GrowthSDG 13: Climate Action